Physiological responses induced by phospholipase C isoform 5 upon heat stress in Arabidopsis thaliana - Annum, Nazish; Ahmed, Moddassir; Tester, Mark; Mukhtar, Zahid; Saeed, Nasir Ahmad (Frontiers in Plant Science, 2023)
Plant’s perception of heat stress involves several pathways and signaling molecules, such as phosphoinositide, which is derived from structural membrane lipids phosphatidylinositol. Phospholipase C (PLC) is a well-known signaling enzyme containing many isoforms in different organisms. In the present study, Phospholipase C Isoform 5 (PLC5) was investigated for its role in thermotolerance in Arabidopsis thaliana. Two over-expressing lines and one knock-down mutant of PLC5 were first treated at a moderate temperature (37 °C) and left for recovery. Then again exposed to a high temperature (45 °C) to check the seedling viability and chlorophyll contents. Root behavior and changes in 32Pi labeled phospholipids were investigated after their exposure to high temperatures. Over-expression of PLC5 (PLC5 OE) exhibited quick and better phenotypic recovery with bigger and greener leaves followed by chlorophyll contents as compared to wild-type (Col-0) and PLC5 knock-down mutant in which seedling recovery was compromised. PLC5 knock-down mutant illustrated well-developed root architecture under controlled conditions but stunted secondary roots under heat stress as compared to over-expressing PLC5 lines. Around 2.3-fold increase in phosphatidylinositol 4,5-bisphosphate level was observed in PLC5 OE lines upon heat stress compared to wild-type and PLC5 knock-down mutant lines. A significant increase in phosphatidylglycerol was also observed in PLC5 OE lines as compared to Col-0 and PLC5 knock-down mutant lines. The results of the present study demonstrated that PLC5 over-expression contributes to heat stress tolerance while maintaining its photosynthetic activity and is also observed to be associated with primary and secondary root growth in Arabidopsis thaliana.